The Homeschool Choice : Parents and the Privatization of Education - Averett, Kate Henley; Averett, Kate Henley (Book collections on Project MUSE., 2021)
The surprising reasons parents are opting out of the public school system and homeschooling their kidsHomeschooling has skyrocketed in popularity in the United States: in 2019, a record-breaking 2.5 million children were being homeschooled. In The Homeschool Choice, Kate Henley Averett provides insight into this fascinating phenomenon, exploring the perspectives of parents who have chosen to homeschool their children. Drawing on in-depth interviews, Averett examines the reasons why these parents choose to homeschool, from those who disagree with sex education and LGBT content in schools, to others who want to protect their children's sexual and gender identities. With eye-opening detail, she shows us how homeschooling is a trend being chosen by an increasingly diverse subset of American families, at times in order to empower-or constrain-children's gender and sexuality. Ultimately, Averett explores how homeschooling, as a growing practice, has changed the roles that families, schools, and the state play in children's lives. As teachers, parents, and policymakers debate the future of public education, The Homeschool Choice sheds light on the ongoing struggle over school choice.